ENGLISH FOR NURSING: A NEED ANALYSIS OF CONTEXTUAL-BASED LANGUAGE TEACHING: ENGLISH FOR NURSING: A NEED ANALYSIS OF CONTEXTUAL-BASED LANGUAGE TEACHING - Tri Susmita Sari; Mualimin (SOSIOEDUKASI, 2026)
English for Nursing is a relatively interesting specialization within the field of English for Specific Purposes (ESP). A deeper understanding of nursing discourse and the creation of a taxonomy of language use in nursing have been made possible through various needs analysis studies. To create appropriateness in evaluating nursing students who use English as a Foreign Language (EFL), this study focused on specific research areas. The research instruments used were interviews and pre-tests to measure students' abilities and needs related to the material and skills focus to be applied during the learning process. The results will assist instructors in various planning decisions, student grouping, selection of learning strategies and activities, and utilization of students' strengths and motivations in ESP classes. The Present Situation Analysis (PSA) component of the students indicated that students lacked several skills, including vocabulary, speaking, and reading. Therefore, as the stage of Target Situation Analysis (TSA), this analysis produces a syllabus design that is adjusted to the realm of English for Specific Purposes (ESP). So that it contributes to the development of effective and efficient learning.